Experimental Study on the Dynamic Modulus and Damping Ratio of Compacted Loess under Circular Dynamic Stress Paths. (14th October 2021) - Yang, Liguo; Shao, Shengjun; Wang, Zhi
Abstract : Dynamic loads such as earthquakes and traffic will simultaneously generate vertical dynamic stress and horizontal shear stress in the foundation soil. When the vertical dynamic stress amplitude is twice the horizontal shear dynamic stress amplitude, and the phase difference between them is 90°, a circular dynamic stress path is formed in the τ z θ d ∼ σ zd − σ θ d / 2 stress coordinate system. To simulate the stress state of soil in the area of the circular dynamic stress path caused by bidirectional dynamic stress coupling, a series of tests of compacted loess under the action of a circular dynamic stress path were carried out using a hollow cylindrical torsion shear apparatus. The effects of the mean principal stress, dry density, and deviatoric stress ratio (the ratio of deviator stress to average principal stress) on the dynamic modulus and damping ratio of compacted loess were mainly studied. The test results show that, under the action of the circular dynamic stress path, the larger the mean principal stress is, the larger the dynamic compression modulus and dynamic shear modulus are. The dynamic compression modulus increases obviously with increasing dry density, but the dynamic shear modulus increases only slightly. When the deviator stress ratio increases from 0 to 0.4, the dynamic compression modulus and dynamic shear modulus increase to a certain extent. In addition, the greater the dry density and deviatoric stress ratio are, the greater the initial dynamic compression modulus and initial dynamic shear modulus of the compacted loess. The dynamic compression damping ratio of compacted loess increases with increasing mean principal stress, but the dynamic shear damping ratio decreases with increasing mean principal stress. Dry density basically has no effect on the dynamic compression damping ratio and dynamic shear damping ratio of compacted loess. When the dynamic strain exceeds 1%, the greater the deviatoric stress ratio is, the smaller the dynamic compression damping ratio and the dynamic shear damping ratio are. The research results can provide reference for the study of dynamic modulus and damping ratio of loess under special stress paths.